Occupational participation and quality of life among persons with paraplegia spinal cord injury in Pakistan / Faizan Jameel Khanzada - Khanzada, Faizan Jameel (2024)
A high number of Spinal Cord Injury (SCI) incidents in young adults aged from 26 to 35 years were reported in Pakistan. Around 90% of these persons, after discharge from the hospital to the community, experience various challenges and find difficulty in occupational participation in the community which negatively affects their Quality of Life (QOL). Previous research on this topic in Western countries, there is a lack of information about this issue in Pakistan. Occupational participation is a significant occupational therapy outcome for persons with paraplegia SCI, improvement health, well-being, and overall QOL. Occupational participation means to involvement in daily life situations such as work, play, and learning and can be assessed by the daily living activities and social roles they undertake. In Pakistan, it was noticed that occupational therapists often do not prioritize occupational participation as a primary outcome in their interventions for persons with paraplegia SCI. Instead, they typically use a medical model managing SCI impairments, aiming to alleviate symptoms resulting in persons who are restricted in their occupation, have fewer chances of thriving, suffer social exclusion, and achieve less independence in the community. Therefore, this study aimed to investigate the occupational participation and QOL of persons with paraplegia SCI in Pakistan using a cross-sectional design. Data was collected using socio-demographic questionnaires, the American Spinal Injury Association Impairment Scale (ASIA scale), the World Health Organization Quality of Life BREF Scale (WHOQOL-BREF scale), the World Health Organization Disability Schedule 2.0 Scale (WHODAS-II scale), and Craig Hospital Inventory of Environmental Factors Scale (CHIEF scale).